Psychological happiness and its relationship to level of ambition among students of Faculty of Education at the University of Zakho - evening studies (Journal of the College of Education for Women, 2024)
The current research aims to identify the level of psychological happiness and the level of ambition among students of the Faculty of Education at the University of Zakho\Evening Studies, to identify the relationship between these two levels, and to identify the statistically significant differences between them according to the variables: gender, age, economic status, among students of the Faculty of Education, Evening Studies. To achieve the objectives of the study, the researcher followed the descriptive approach appropriate for this study. The sample of the current research included (125) male and female students. The study tools were represented in two scales: the psychological happiness scale, which contains (27) paragraphs, and the level of ambition scale, which contains (27) paragraphs prepared by Samawi and Shaheen (2019). After verifying the validity and reliability of the tools, they were applied to achieve the objectives of the current research. The data were analyzed using the (SPSS) program. The current research reached the following results: There are differences between the level of psychological happiness and the level of ambition among all students, the existence of statistically significant differences in psychological happiness according to the gender variable, in favor of males, and there is no difference between the individuals of the research sample in the level of ambition according to the gender variable. In light of the results reached by the current research, it makes some recommendations and suggestions.